2005
DOI: 10.1038/sj.eye.6701917
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pterygium and cataract in indigenous populations of the Brazilian Amazon rain forest

Abstract: Purpose To compare the prevalence of pterygium and cataract in four indigenous populations of the Brazilian Amazonian rain forest (Arawak, Tukano, Maku, and Yanomami) with different ethnic and social behaviour backgrounds. Methods A cross-sectional pterygium and cataract survey was performed in 624 adult Indians of the Brazilian rain forest belonging to four different ethnic groups. The Indians were classified according to their social behaviour in two groups: Arawak and Tukano (group 1) and Maku and Yanomami … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
41
2
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 17 publications
6
41
2
4
Order By: Relevance
“…These results are similar to those by other studies, and most of them confirm that there is a correlation between pterygium and age. [4][5][6][11][12][13][15][16][17] In this study, we found that a VA worse than 20/40 in the better eye is five times more likely among people with pterygium, and although this factor has been assessed in a limited number of studies, they support our findings. This can be due to a change in the convexity of the cornea and development of astigmatism.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…These results are similar to those by other studies, and most of them confirm that there is a correlation between pterygium and age. [4][5][6][11][12][13][15][16][17] In this study, we found that a VA worse than 20/40 in the better eye is five times more likely among people with pterygium, and although this factor has been assessed in a limited number of studies, they support our findings. This can be due to a change in the convexity of the cornea and development of astigmatism.…”
Section: Discussionsupporting
confidence: 81%
“…Some reports indicate that pterygium prevalence rates are lower than 2.0% where Compared to almost all other studies, the prevalence of pinguecula is relatively low in Tehran, and the only report indicating similar results concerns a study in Australia with a prevalence of 1.2% in Melbourne. 4 In contrast to the studies in Tehran and Melbourne, higher prevalence rates have been reported in other populations; 6,7,[11][12][13][14][15][16][17] even as high as 33.1 and 23% in China and Carolina, respectively (Table 4). 5,14 In this study, the prevalence of pterygium according to gender was higher in men only in the 20-to 39-year-old age group, and no significant correlation was seen between pterygium and gender in other age groups.…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…According to the reports, a pterygium prevalence of 12.8 % from total Indian population (11) and 18.4 % among elderly and adults was described. Furthermore, pterygium lesions were found mainly in Indian groups with higher UV exposure (12) . The objective of this study is to evaluate pterygium prevalence and characteristcs in small communities of the Amazon rainforest located along the Solimões and Japurá rivers, state of Amazonas, Brazil (Figure 1).…”
mentioning
confidence: 99%
“…Prevalence of this connective tissue growth over cornea in this population (26.2%) was much higher than the worldwide rate (10.2%). [39] Very few published studies reported greater prevalence of pterygium: 33.01% in Doumen County, China [40]; 30.8% in Kumejima Island, Japan [41]; and 36.6% in Arawak and Tukano indian communities from Amazon forest [42]. Rural environment, low geographical latitude of Conceição das Crioulas and preponderance of black ethnicity among quilombolas may contribute to the high prevalence.…”
Section: Discussionmentioning
confidence: 99%